Fear conditioned changes of heart rate in patients with medial cerebellar lesions. Issue 1 (1st January 2002) - Maschke, M; Schugens, M; Kindsvater, K; Drepper, J; Kolb, F P; Diener, H-C; Daum, I; Timmann, D
Abstract : Fear conditioned changes of heart rate and skin conductance responses were investigated in patients with medial cerebellar lesions. A classical conditioning paradigm with a tone as the conditioned stimulus (CS) and an electrical shock as the unconditioned stimulus (US) was tested on five patients with medial cerebellar lesions due to surgery for astrocytoma and five controls. The CS preceded the US by 5900 ms and coterminated with the US. Changes in heart rate and skin conductance responses were obtained as measures for autonomic fear responses. Effects of conditioning were quantified by comparison of the habituation and extinction phases. Controls, but not cerebellar patients, showed a significant decrease of heart rate during fear conditioning. However, there were no significant fear conditioned changes in electrodermal responses in either group. In summary, the medial cerebellum seems to be involved in fear-conditioned bradycardia in humans.